A Novel Field Transplantation Technique Reveals Intra-Specific Metal-Induced Oxidative Responses in Strains of Ectocarpus Siliculosus with Different Pollution Histories - Moenne-Munoz, A; Contreras-Arredondo, R; Gonzalez-Figueroa, A (Elsevier Ltd, 2015)
A novel field transplantation technique, in which seaweed material is incorporated into dialysis tubing, was used to investigate intra-specific responses to metals in the model brown alga Ectocarpus siliculosus. Metal accumulation in the two strains was similar, with higher concentrations in material deployed to the metal-contaminated site (Ventanas, Chile) than the pristine site (Quintay, Chile). However, the oxidative responses differed. At Ventanas, strain Es147 (from low-polluted site) underwent oxidative damage whereas Es524 (from highly polluted site) was not affected. Concentrations of reduced ascorbate (ASC) and reduced glutathione (GSH) were significantly higher in Es524. Activities of the antioxidant enzymes superoxide dismutase (SOD), ascorbate peroxidase (APX), catalase (CAT), and glutathione reductase (GR) all increased in Es524, whereas only SOD increased in Es147. For the first time, employing a field transplantation technique, we provide unambiguous evidence of inter-population variation of metal-tolerance in brown algae and establish that antioxidant defences are, in part, responsible. © 2015 Elsevier Ltd. All rights reserved.